Polymorphism of microsattelite loci within the grape germplasm collection maintained at the Dagestan Experiment Station of VIR - M. M. Agakhanov; V. A. Volkov; P. S. Ulianich; K. M. Abdullaev; E. N. Kislin (Труды по прикладной ботанике, генетике и селекции, 2019)
Background. Ampelographical collection of the VIR experiment station in Dagestan comprises 320 accessions of grape cultivars and 25 ecotypes of wild grape species, that are highly polymorphic in their morphological traits. As for any other large germplasm collections, the problem of genetic identification of the accessions and their originality is critical for the ampelographical collection. Genome of Vitis vinifera L. contains many polymorphic microsatellite loci, their allele diversity could be used to reveal the genetic structure of the ex situ collection as well as for the identification of duplicates. The task of the study was to estimate the level of polymorphism of four microsatellite loci that were previously recommended for the genotyping purposes in grape. The grape collection of Dagestan experiment station of VIR was investigated.Materials and methods. The analysis of microsatellite loci was based on PCR with the primers that were published previously. The size of alleles was estimated with Nanophor 05 sequencer (Syntol, Moscow). The results of the collection screening with the microsatellite markers were analyzed with Structure 2.3.4 software. The main characteristics of microsatellite loci (Polymorphic Information Content, heterozygosity) were determined using GenAlEx 6.2 program.Results and conclusion. The high level of polymorphism of the microsatellite loci VVS2, VVMD27, VVMD31, VVMD28 were detected when studying 221 accessions of the grape collection at the Dagestan experiment station. Heterozygosity of the loci was 0,50-0,83, the number of alleles per locus varied between 17 and 19, in total 70 alleles was detected. No relationship was detected between the allele combinations of accessions and their eco-geographical origin or any particular cultivar group. To reveal the genetic structure of the grape germplasm collection the larger number of SSR loci should be involved.